2017
DOI: 10.1596/1813-9450-8206
|View full text |Cite
|
Sign up to set email alerts
|

Trade Creation and Trade Diversion in Deep Agreements

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 22 publications
(31 reference statements)
4
73
0
1
Order By: Relevance
“…Our results also suggest that this change in the fundamentals of developing countries’ growth was enabled by, among other, major changes in population dynamics, including high level of urbanisation and global trade—notably the emergence of international value chains. International value chain links are stronger between countries that have trade agreements, and more so deeper trade agreements (Mattoo, Mulabdic, & Ruta, ). This explains the shift from simple commodity dependent exports to more diversified baskets within the value chains and trade agreements.…”
Section: Resultsmentioning
confidence: 99%
“…Our results also suggest that this change in the fundamentals of developing countries’ growth was enabled by, among other, major changes in population dynamics, including high level of urbanisation and global trade—notably the emergence of international value chains. International value chain links are stronger between countries that have trade agreements, and more so deeper trade agreements (Mattoo, Mulabdic, & Ruta, ). This explains the shift from simple commodity dependent exports to more diversified baskets within the value chains and trade agreements.…”
Section: Resultsmentioning
confidence: 99%
“…The data set provides information on the detailed content of 279 RTAs, signed by 180 countries between 1957 and 2015. Following Mattoo et al (2017), we measure the depth of an agreement as the count of strictly enforceable provisions included in the RTA. 8 Other dimensions of the content of RTAs used in the analysis include the presence of regulatory provisions and the preferential or nondiscriminatory nature of provisions.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…5 It has been shown that tariff erosion can be a factor behind the multiplication of RTAs (Baldwin and Jaimovich, 2012;Chen and Joshi, 2010). In contrast, Mattoo, Mulabdic, and Ruta (2017) analyze the content of trade agreements and find that some provisions included in deep agreements have a public good aspect, as they increase trade also with nonmembers. This paper provides firm-level evidence on the positive spillover effects of deep trade agreements on firms' entry and export decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Pacific and Caribbean countries can be expected to gain more from their current preferential trade agreements than Atlantic countries (figure 26). Deep agreements, covering a larger number of policy areas, have been shown to lead to more trade creation and less trade diversion than shallow agreements (Mattoo et al 2017). They are also associated with more trade related to global value chains (Laget et al 2018;Orefice and Rocha 2014).…”
Section: Who You Trade With Mattersmentioning
confidence: 99%